Mechanical Behavior of Layered Composite Structures of Aluminum Foam Partially Filled with Polyamide - Du, Wanrong; Orbulov, Imre Norbert; Tamás-Bényei, Péter; Kádár, Csilla (Periodica polytechnica. Mechanical engineering - Mas̆inostroenie, 2025)
In this study, the mechanical properties of layered composite structures were investigated. We achieved the layered structure by hot-pressing 1 mm, 3 mm, or 5 mm thick polyamide 6 (PA) sheets into the pores on the top and bottom sides of an open-cell metal foam at 240 °C and 15 MPa (150 bar). The PA-infiltrated depths varied with the thickness of the hot-pressed PA sheets. According to the bending and post-impact bending tests, flexural strengths improved as the infiltration depth of PA increased. Compared to the metal foam, a maximum of 15% increase in flexural strength and a 400% increase in residual flexural strength were measured. However, using a 1 mm thick PA sheet lowered the flexural strength of the open-cell metal foam. We found that the 1 mm thick PA sheet failed to fully infiltrate the foam pores, resulting in residual voids at the metal-PA interface, which caused premature fracture during bending.